Photochemical Mechanism of an Atypical Algal Phytochrome. (20th April 2018) - Choudry, Uzma; Heyes, Derren J.; Hardman, Samantha J. O.; Sakuma, Michiyo; Sazanovich, Igor V.; Woodhouse, Joyce; De La Mora, Eugenio; Pedersen, Martin N.; Wulff, Michael; Weik, Martin; Schirò, Giorgio; Scrutton, Nigel S.
Abstract: Phytochromes are bilin‐containing photoreceptors that are typically sensitive to the red/far‐red region of the visible spectrum. Recently, phytochromes from certain eukaryotic algae have become attractive targets for optogenetic applications because of their unique ability to respond to multiple wavelengths of light. Herein, a combination of time‐resolved spectroscopy and structural approaches across picosecond to second timescales have been used to map photochemical mechanisms and structural changes in this atypical group of phytochromes. The photochemistry of an orange/far‐red light‐sensitive algal phytochrome from Dolihomastix tenuilepis has been investigated by using a combination of visible, IR and X‐ray scattering probes. The entire photocycle, correlated with accompanying structural changes in the cofactor/protein, are reported. This study identifies a complex photocycle for this atypical phytochrome. It also highlights a need to combine outcomes from a range of biophysical approaches to unravel complex photochemical and macromolecular processes in multi‐domain photoreceptor proteins that are the basis of biological light‐mediated signalling. Abstract : Atypical phytochrome photochemistry : Phytochromes have become attractive targets for optogenetic applications because of their ability to respond to multiple wavelengths of light. A combination of time‐resolved visible, IR, and X‐ray scattering techniques have been used across picosecond to second timescales to map photochemical mechanisms and structural changes in an atypical orange/far‐red light‐sensitive algal phytochrome.